Retrieving aerosol microphysical properties by Lidar‐Radiometer Inversion Code (LIRIC) for different aerosol types. Issue 8 (24th April 2014) - Granados‐Muñoz, M. J.; Guerrero‐Rascado, J. L.; Bravo‐Aranda, J. A.; Navas‐Guzmán, F.; Valenzuela, A.; Lyamani, H.; Chaikovsky, A.; Wandinger, U.; Ansmann, A.; Dubovik, O.; Grudo, J. O.; Alados‐Arboledas, L.
Abstract LIRIC (Lidar‐Radiometer Inversion Code) is applied to combined lidar and Sun photometer data from Granada station corresponding to different case studies. The main aim of this analysis is to evaluate the stability of LIRIC output volume concentration profiles for different aerosol types, loadings, and vertical distributions of the atmospheric aerosols. For this purpose, in a first part, three case studies corresponding to different atmospheric situations are analyzed to study the influence of the user‐defined input parameters in LIRIC when varied in a reasonable range. Results evidence the capabilities of LIRIC to retrieve vertical profiles of microphysical properties during daytime by the combination of the lidar and the Sun photometer systems in an automatic and self‐consistent way. However, spurious values may be obtained in the lidar incomplete overlap region depending on the structure of the aerosol layers. In a second part, the use of a second Sun photometer located in Cerro Poyos, in the same atmospheric column as Granada but at higher altitude, allowed us to obtain LIRIC retrievals from two different altitudes with independent Sun photometer measurements in order to check the self‐consistency and robustness of the method. Retrievals at both levels are compared, providing a very good agreement (differences below 5 µm3/cm3) in those cases with the same aerosol type in the whole atmospheric column. However, some assumptions such as the height independency of parameters (sphericity, size distribution, or refractive index, among others) need to be carefully reviewed for those cases with the presence of aerosol layers corresponding to different types of atmospheric aerosols.